2022
DOI: 10.3389/fimmu.2022.1013186
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events of immune checkpoint inhibitors for patients with digestive system cancers: A systematic review and meta-analysis

Abstract: ObjectiveTo study the incidence and distribution of adverse events in immune checkpoint inhibitors (ICI) for digestive system cancers and to provide a reference for the safe, rational, and effective use of immune detection site inhibitors.MethodsWe searched for articles published in English between January 1, 2010, and May 18, 2022. All clinical trials of ICI-based therapies for digestive system cancers were investigated, including only randomized controlled trials that reported data on the overall incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Most immunotherapy-related adverse effects were manageable, some resolving after treatment discontinuation, and others responding well to corticosteroid therapy. Overall, neoadjuvant immunotherapy in HCC demonstrated safety akin to previous studies in gastrointestinal tumors ( 39 ).Furthermore, the highest occurrence rate of grade 3-4 adverse events reported in this study was 43% (reported by Kaseb, A.O. et al.…”
Section: Discussionsupporting
confidence: 71%
“…Most immunotherapy-related adverse effects were manageable, some resolving after treatment discontinuation, and others responding well to corticosteroid therapy. Overall, neoadjuvant immunotherapy in HCC demonstrated safety akin to previous studies in gastrointestinal tumors ( 39 ).Furthermore, the highest occurrence rate of grade 3-4 adverse events reported in this study was 43% (reported by Kaseb, A.O. et al.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have hypothesized that the reason for this low incidence may be because of significant heterogeneity and unobserved confounders such as the disease site, concomitant therapies, and other concomitant medications [14]. Additionally, others considered irAEs to be influenced by many factors including, but not limited to, age, BMI, smoking, comorbidities, and performance status (PS) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the favorable clinical benefits of checkpoint inhibition, it has side effects known as immune-related adverse events (irAEs) (13,14). IrAEs include skin diseases, diarrhea, hepatotoxicity, and cardiotoxicity (15)(16)(17)(18)(19). Checkpoint inhibition may also cause fulminant or fatal toxic reactions (20).…”
Section: Introductionmentioning
confidence: 99%